Qur’anic Foundations of Religious Moderation: A Case Study of Students at UIN Raden Mas Said Surakarta - Ari Hikmawati; Moh Abdul Kholiq Hasan (Jurnal Studi Al-Qur'an, 2026)
Recent national surveys in Indonesia, including reports from the Ministry of Religious Affairs and independent research institutions, indicate a decline in religious tolerance among students, raising concerns about the effectiveness of religious education in fostering religious moderation. This study examines the Qur’anic foundations of religious moderation by mapping students’ understanding of selected Qur’anic verses on tolerance and analyzing their relationship with religious moderation among students at UIN Raden Mas Said Surakarta. In this study, mapping refers to an empirical assessment of students’ perceptions and comprehension of tolerance-related Qur’anic verses and their association with moderating religious attitudes. Employing a quantitative survey design, data were collected from 352 students across five faculties using stratified systematic sampling. Correlation and regression analyses were applied to examine the relationship between the variables. The findings reveal a positive and statistically significant relationship between students’ understanding of Qur’anic tolerance verses and religious moderation (r = 0.505, p < 0.01), indicating a moderate strength of association. Regression analysis further confirms the model's robustness. The results suggest that stronger comprehension of Qur’anic principles of tolerance is associated with higher levels of religious moderation, shaped by curricular content, lecturers’ pedagogical approaches, and students’ social environments. These findings provide empirical support for strengthening Qur’an-based educational policies and instructional strategies to promote religious moderation within State Islamic Higher Education Institutions (PTKIN).